THE BENEFITS OF ZIRCONIUM CROWNS VERSUS STAINLESS STEEL CROWNS IN PEDIATRIC DENTISTRY. A REVIEW ARTICLE - Vasilica Toma; Ana Sîrghe; Stefan-Alexandru Trufanda; Constantin Luca; Vacariu Simina Mădălina; Carmen Savin (Romanian Journal of Oral Rehabilitation, 2024)
Objectives: This study aims to provide a current overview of the clinical outcomes and advantages of zirconia pediatric crowns compared to traditional stainless steel crowns. Material and method: We evaluated articles from the MedLine database, researched via PubMed, ScienceDirect and EBSCO using MeSH terms. Results: Stainless steel crowns have long been considered the „gold standard” for full-coverage restorations in primary molars due to their simplicity in preparation, durability, and strength. However, their primary limitation is their aesthetic appearance. In contrast, zirconia crowns, which are tooth-colored full crowns, provide an excellent aesthetic solution and are more effective in maintaining and promoting gingival health. Conclusion: Zirconia pediatric crowns currently represent the best restoration option, offering all the benefits of prefabricated stainless steell crowns while also providing exceptional aesthetics that fully satisfy today’s beauty standards.